2018
DOI: 10.1021/jacs.8b10233
|View full text |Cite
|
Sign up to set email alerts
|

Selective Ruthenium-Catalyzed Transformation of Carbon Dioxide: An Alternative Approach toward Formaldehyde

Abstract: Formaldehyde is an important precursor to numerous industrial processes and is produced in multimillion ton scale every year by catalytic oxidation of methanol in an energetically unfavorable and atom-inefficient industrial process. In this work, we present a highly selective one-step synthesis of a formaldehyde derivative starting from carbon dioxide and hydrogen gas utilizing a homogeneous ruthenium catalyst. Here, formaldehyde is obtained as dimethoxymethane, its dimethyl acetal, by selective reduction of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 58 publications
(37 reference statements)
4
75
0
Order By: Relevance
“…In detail, one molecular ruthenium catalyst allowed the sequential reduction and acetalization transformation . Subsequent optimization studies using the established catalyst lead structure allowed reactions with increased TONs . Additionally, a non‐precious and efficient cobalt‐triphos system could be established for this hydrogenation sequence of CO 2 to DMM .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In detail, one molecular ruthenium catalyst allowed the sequential reduction and acetalization transformation . Subsequent optimization studies using the established catalyst lead structure allowed reactions with increased TONs . Additionally, a non‐precious and efficient cobalt‐triphos system could be established for this hydrogenation sequence of CO 2 to DMM .…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the present investigation with formic acid was initiated with this [Ru(triphos)(tmm)] catalyst and aluminum tris(trifluoromethanesulfonate) Al(OTf) 3 as Lewis acidic co‐catalyst. The Al(OTf) 3 acid was selected for this work as it showed the best results of previous reported work on DMM synthesis from CO 2 . Generally, first reactions were carried out using molecular hydrogen at a pressure of 80 bar and 80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, the group of Trapp used the developed catalyst lead structure and prepared catalysts derivatives (ruthenium/N‐triphos/Al(OTf) 3 ) in combination with consequent optimization of the reaction conditions for OME 1 and MF synthesis from CO 2 /H 2 and methanol. The authors extensively investigated the effects of variations in the reaction conditions with respect to temperature, partial pressure of H 2 and CO 2 , reaction time, and additive as well as catalyst and Lewis acid concentration. Consequently, the optimized conditions resulted in the formation of OME 1 and MF in TONs of 786 and 533 (Scheme ).…”
Section: One Step Synthesis Of Ome1from the Direct Hydrogenation Of Cmentioning
confidence: 99%
“…25,26 Recently, we applied a univariate optimisation approach including several hundred catalytic reactions to improve the selective ruthenium-catalysed transformation of carbon dioxide to dimethoxymethane (DMM) reaching a turnover number (TON) of 786 (Scheme 1). 27,28 The product DMM itself is a high value feedstock for biofuels, but can also be hydrolysed yielding formaldehyde and methanol or directly employed as a formaldehyde synthon. 29,30 Beside the desired product, only methyl formate (MF) was formed with TONs of up to 1290 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Beside the desired product, only methyl formate (MF) was formed with TONs of up to 1290 (Scheme 1). 27 Previously, two studies on the selective hydrogenation of CO 2 by the group of Klankermayer showed the formation of DMM and MF by using a homogeneous ruthenium catalyst 31 with TONs of 214 and 104 or a cobalt catalyst 32 with TONs of 157 and 37, respectively. Further selective reductions toward the formaldehyde oxidation state were reported utilising hydroboration, [33][34][35][36][37] hydrosilylation, 38,39 and frustrated Lewis pairs, 40,41 however, being mainly of academic interest due to the stoichiometric use of reducing reagents.…”
Section: Introductionmentioning
confidence: 99%